(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Abstract search seeks to clarify the role and the importance of financial and fiscal policy adopted by the Iraqi Government during the years (2015 – 2018) to meet federal public deficit, as the Iraqi economy to shocks from falling global oil prices and terrorist attack ISIS, so the State budget suffered from a severe lack of income as a result of its reliance on revenues from selling crude oil and in return the high proportion of public expenditures. Especially military to counter these attacks that by studying the results of the implementation of budgets and analysis and statement Causes of disabilities and assessment of these policies and procedures imposed by the International Monetary Fund. the research aims to show how increased general State revenues, as well as how to relieve public deficit through adherence to financial and fiscal policies imposed by the IMF. The extent the contribution and importance of Iraq’s commitment to implement IMF conditions to mitigate the deficit of the State budget. One of the main conclusions reached by the Iraqi Government to issue laws federal budget of the State, for years (2015, 2016, 2017, 2018) disability scheme, and this decision taken under certain conditions according to meticulous studies in selected, which does not apply the top developed countries, have not been Statement by external borrowing amounts by the Iraqi Government to meet the deficit didn’t chart are shown in the balance sheet of the Republic of Iraq within the account, and not recorded in the accounting records of the Treasury but statistically the public debt, and control Bureau Federal financial numbered book (10505) on 22/5/2017. and highlighted the recommendations reached by search account that the Iraqi Government is preparing economic studies in order to estimate the revenues and expenditures are closer to reality to document the results of the implementation of previous years with Current, and expected future developments and non-disability publication scheme, and the need for external borrowing amounts in the statement of financial position of the Republic of Iraq and recorded in the accounting records of the Treasury.